Bunering apabiliti of B-chloropropionic Acid-Sodium B-chloropropionate Slstellin Acidic Geotherllal Brine - Yolanda P. Brondial (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
The Philippines, being part of the Pacific